2017
DOI: 10.1194/jlr.m070714
|View full text |Cite
|
Sign up to set email alerts
|

Regional changes in CNS and retinal glycerophospholipid profiles with age: a molecular blueprint

Abstract: We present here a quantitative molecular blueprint of the three major glycerophospholipid (GPL) classes, phosphatidylcholine (PC), phosphatidylserine (PS), and phosphatidylethanolamine (PE), in retina and six regions of the brain in C57Bl6 mice at 2, 10, and 26 months of age. We found an age-related increase in molecular species containing saturated and monoenoic FAs and an overall decrease in the longer-chain PUFA molecular species across brain regions, with loss of DHA-containing molecular species as the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 120 publications
0
31
0
Order By: Relevance
“…The methods have been described previously 35 , 36 . Briefly, ROSs were diluted 1 : 40 with 2-propanol/methanol/chloroform (4 : 2 : 1 v/v/v) containing 20 mM ammonium formate and 1.00 µM PC 14 : 0/14 : 0, 1.00 µM PE 14 : 0/14 : 0, and 0.33 µM PS 14 : 0/14 : 0 as internal standards.…”
Section: Methodsmentioning
confidence: 99%
“…The methods have been described previously 35 , 36 . Briefly, ROSs were diluted 1 : 40 with 2-propanol/methanol/chloroform (4 : 2 : 1 v/v/v) containing 20 mM ammonium formate and 1.00 µM PC 14 : 0/14 : 0, 1.00 µM PE 14 : 0/14 : 0, and 0.33 µM PS 14 : 0/14 : 0 as internal standards.…”
Section: Methodsmentioning
confidence: 99%
“…Data is represented as relative mole percent of each FA species. Additionally, the retinal phospholipid composition was analyzed by methods described previously [ 21 , 48 ]. Briefly, retinas were homogenized in methanol and diluted 1:40 with 2-propanol/methanol/chloroform (4:2:1 v/v/v) containing 20 mM ammonium formate and 1.00 μM PC 14:0/14:0, 1.00 μM phosphatidylethanolamine (PE) 14:0/14:0 and 0.33 μM phosphatidylserine (PS) 14:0/14:0 as internal standards.…”
Section: Methodsmentioning
confidence: 99%
“…ELOVL4 is primarily expressed in skin, testis, retina and brain where it elongates saturated (skin and brain [ 19 21 ]) and polyunsaturated (retina and testis [ 22 – 24 ]) FA. Very long chain saturated fatty acids (VLC-SFAs) and very long-chain poly unsaturated fatty acids (VLC-PUFAs) do not exist as free FA, but rather have their carboxyl terminus linked to a headgroup like e.g.…”
Section: Introductionmentioning
confidence: 99%
“…DHA is also used as a signal transduction molecule, which protects from neuronal damages in oxidative injuries to the retina (Mukherjee et al, ). Phosphatidyletanolamine (PE) and PS work as storage for DHA (LeKim & Betzing, ) and their 40:06; PS (18:0/22:6n3) and PE (18:0/22:6n3) are major molecules in retinal tissue (Hopiavuori et al, ). Our results revealed that expression of several species of PE that include DHA are upregulated in whole TONI retinal tissue (Figure , e, g, h), whereas PE species with mono‐ or di‐unsaturated fatty acids did not change (Figure , a, b, c).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that retinal tissue has highly unique lipids that play critical roles in retinal function (Fliesler & Anderson, ) and are related to diseases such as age‐related macular degeneration (Liu, Chang, Lin, Shen, & Bernstein, ). The phospholipids in retinal tissue have been well characterized by gas chromatography–mass spectrometry (Aveldaño & Bazán, ; Aveldaño & Sprecher, ), electrospray mass spectrometry (Acar et al, ; Berdeaux et al, ; Ford et al, ), and tandem mass spectrometry (Hopiavuori et al, ). The retinal tissue is highly enriched in polyunsaturated fatty acids (PUFAs), with docosahexaenoic acid (DHA) (22:6) (22 carbons with 6 double bonds) accounting for approximately 50% of the fatty acids in the photoreceptors (Fliesler & Anderson, ).…”
Section: Introductionmentioning
confidence: 99%